Factorial screening on the development of cellulose nanocrystal/ carboxylated multi-walled carbon nanotube polyethersulfone membrane for humic acid rejection - Nor Azura, Che Mahmud; Mazrul Nizam, Abu Seman; Mohd Sobri, Takriff; Ang, Wei Lun; Saufia, Syed M. (2022)
A two-level factorial experimental design was used to formulate the dope composition of cellulose nanocrystal (CNC) multi-walled carbon nanotube (MWCNT) polyethersulfone (PES) membrane for humic acid (HA) rejection. Four factors were screened, which are the composition of PES (1517 wt.%), polyvinylpyrrolidone (PVP, 1-4%), CNC (0.01-0.75%), and carboxylated MWCNT (00.025%). The membranes were evaluated based on HA rejection from a 10-ppm aqueous feed solution. The percentage of MWCNT was the most significant factor, accounting for 72.31 % of the contribution. The highest HA rejection of 90% was obtained from the membrane fabricated using 17 % PES, 1% PVP,0.01 % CNC, and 0.025% MWCNT. The predicted values generated from the model agreed reasonably with the experimental data, demonstrating the model's validity.